Changing the face of hockey: A study of the half-visor's ability to reduce the severity of facial injuries of the upper-half of the face among East Coast Hockey League players - Brunn, J. W. (The Physician and Sportsmedicine, 2008)
Objective: The purpose of the study was to identify the effectiveness of half-visors by qualitatively comparing the severity, location, and mechanism of facial injuries involving the upper-half of the face among an equal number of East Coast Hockey League (ECHL) players with and without half-visors. Full visors were not included in the study because ECHL players do not wear full visors. Design: A stratified sample was retrospectively collected from 5 seasons of ECHL players who suffered facial injuries to the upper-half of the face with and without half-visors. The upper-half of the face is the region purported to be protected by the half-visor. A total of 186 injuries were identified to the upper-half of the face (93 wore half-visors and 93 wore no protection). Setting: Johnstown Cambria County War Memorial Arena, Johnstown, PA. Results: High-sticking was the most common mechanism of injury. Injury severity scores for lacerations with standard deviations by injury location (ie, forehead, cheek) were statistically significant in the half-visor group when compared with the no-visor group. The injury severity scores for contusions due to collisions were statistically higher in the no-visor group compared with the half-visor group. Conclusions: Most injury mechanisms occur from an upward trajectory, which could easily slip under the half-visor and strike the upper-half of the face and eye region. The half-visor may not adequately protect the upper-half of the face from common injury mechanisms.